Pediatric obesity: a mini-review for pediatrician - Brambilla, Ilaria; Bellanca, Emanuela; Pistone, Carmelo; De Filippo, Maria; Votto, Martina; Tondina, Enrico; Licari, Amelia; Guarracino, Carmen; Marseglia, Gian Luigi (Acta Biomedica Atenei Parmensis, 2022)
Obesity is a multifactorial disease, and its prevalence in children has been increased over the last 30 years in Italy and many other European Countries. Obesity significantly impacts the quality of life of affected patients and health care systems. Obesity is related to several clinical comorbidities, especially metabolic syndrome and diabetes. The standard of care in this patient is still considered lifestyle changes and a healthy diet with regular physical activity to prevent associated metabolic complications (impaired glucose tolerance and type 2 diabetes) and reduce cardiovascular risk.Therefore, pediatricians should recognize potential risk factors (sedentary lifestyle, sugar, and fats-rich diet, genetic syndromes) and early signs of overweight and obesity to promptly address the child to a pediatric endocrinologist and a specialized reference Center.